Implementation and outcomes of an ambulatory care pharmacist service: Application of an implementation science framework. - Foster, Brooke; Spillane, Jordan; Abuzoor, Anas; Zraik, Mahadi (American Journal of Health-System Pharmacy, 2023)
Purpose As teams work to optimize the pharmacist's role on care teams, it is important to be proactive and strategic during the service creation process. Implementation science frameworks can help guide pharmacists as they work to translate evidence-based interventions into practice. Summary When a care gap in respiratory chronic disease state management in the primary care setting was identified, a team was created to investigate whether an ambulatory care pharmacist service would be a valuable way to address the care gap. This paper outlines the steps taken to scope and implement a new pharmacist service. An implementation science framework, the Exploration, Preparation, Implementation, Sustainment (EPIS) framework, was used to guide the service implementation process. Postimplementation data were collected to assess the impact of the service. A total of 56 patients were managed by the pharmacist in the first year following implementation. Data suggested that the pharmacist service has clinical value based on an improvement in chronic obstructive pulmonary disease (COPD) symptom control, rescue inhaler use, adherence, and inhaler technique. The data also informed postimplementation changes for continuous quality improvement. Conclusion The use of an implementation science framework to implement a new pharmacist service proved valuable. Although this project focused on addressing a care gap in COPD, implementation science frameworks can and should be used to guide the implementation of a variety of new clinical services to enhance impact and sustainability.